2013
DOI: 10.1111/jocn.12467
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and fear in patients with short waiting times before coronary artery bypass surgery – a qualitative study

Abstract: The detailed insight into the emotional experiences of patients with a short waiting time before coronary artery bypass grafting surgery is a basis for targeted anxiety-reducing interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
5

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 18 publications
1
24
0
5
Order By: Relevance
“…Keleto kitų tyrimų metu nustatyta, kad pacientai, kurie ilgiau laukia operacijos, jaučia nerimą priešoperaciniu laikotarpiu. Mažiausias nerimo lygmuo (2,8 balo) nustatytas respondentams, kurie apie operaciją sužino likus savaitei iki operacijos [14,4].…”
Section: Rezultatų Aptarimasunclassified
See 1 more Smart Citation
“…Keleto kitų tyrimų metu nustatyta, kad pacientai, kurie ilgiau laukia operacijos, jaučia nerimą priešoperaciniu laikotarpiu. Mažiausias nerimo lygmuo (2,8 balo) nustatytas respondentams, kurie apie operaciją sužino likus savaitei iki operacijos [14,4].…”
Section: Rezultatų Aptarimasunclassified
“…Iš dalies respondentams nerimą kėlė tai, kad operacijos metu paaiškės, jog serga nepagydoma liga, išvaizdos pokyčiai po operacijos. Keletas kitų tyrimų taip pat tyrė priešoperacinio nerimo priežastis ir jų metu buvo nustatyta, kad respondentai nerimauja prieš operaciją dėl: baimės numirti, skausmo, kurį gali pajusti operacijos metu, komplikacijų po operacijos, pooperacinio skausmo, artimųjų gerovės [17,16,4,11].…”
Section: Rezultatų Aptarimasunclassified
“…Various sources of preoperative anxiety affecting patients on the day before CABG were explored in a precedent study (Feuchtinger et al 2014). We found that patient concerns were reflected in the 'State-Trait Operation Anxiety' (STOA) inventory (Krohne et al 2005).…”
Section: Outcomes Measuresmentioning
confidence: 99%
“…Various sources of anxiety and fear were explored in a precedent study at our hospital. The concerns most frequently voiced were nonspecific fear or uncertainty, fear of medical intervention, medical objects or the intensive care unit (ICU), fear of immobility or restriction and fear of complications or failure of the surgery (Feuchtinger et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…O pré-operatório para coronariopatas configura-se como um momento estressante uma vez que há sentimentos de medo relacionados a complicações pós-cirúrgicas, a restrições e imobilidade, à dor e a problemas com o sono de acordo com o identificado entre pacientes alemães (14). Além disso, o paciente se preocupa consigo, sente medo da morte e pode enfrentar problemas econômicos e relacionados ao trabalho e à família conforme identificado entre pacientes iranianos (15).…”
Section: Introductionunclassified